Aluminum alloy powder for additive manufacturing and preparation method and application thereof
By using AltixfeynizComzrn alloy particles and aluminum alloy powder composed of thin slices, combined with induction melting, atomization, and ball milling technology to generate layer layer ALN phase, solve the difficulty of high heat conduction and high heating and high high heat conductive and high in the manufacture of additive manufacturing. The problem of intensity realizes the advanced manufacturing of high -performance aluminum alloy components.
Patent Information
- Application Number
- CN202411385112.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Existing aluminum alloy powders are difficult to achieve high thermal conductivity and high strength at the same time in additive manufacturing, and are prone to cracking sensitivity, which fails to meet the high-performance needs in aerospace and other fields.
The aluminum alloy powder composed of AltixfeynizComzrn alloy particles and an aluminum alloy powder composed of ALN thin slices covered with its surface is prepared by induced melting and high -pressure nitrogen atomization technology to combine the ball milling process.
The high thermal conductivity coefficients (193-218W/(m · K) and high yield strength (652MPa ~ 693MPa) are implemented in the aluminum alloy sample, while maintaining good toughness to meet the weight loss needs of aerospace and other fields.
Smart Images

Figure CN118880121B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of additive manufacturing, and specifically relates to an aluminum alloy powder for additive manufacturing, a preparation method and an application thereof. Background Art
[0002] Additive Manufacturing (AM) technology is a new manufacturing technology based on the principle of layered manufacturing. It uses the method of accumulating materials layer by layer to directly manufacture digital models into physical parts. Compared with traditional manufacturing technology, AM technology has a series of advantages such as high flexibility, no molds, short cycle, and no restrictions on part structure and materials. It has been widely used in aerospace, automobile, electronics, medical, military and other fields. Laser additive manufacturing (LAM) technology includes laser solid forming (LSF) technology with synchronous material feeding as the main technical feature and laser selective melting (SLM) technology with powder bed as the main technical feature. Selective laser melting (SLM) technology uses a high-energy laser to melt a thin layer of powder (usually 20 to 50 μm thick) based on a powder bed that is finely spread layer by layer and laser-fused and deposited layer by layer to form high-density components of any complex shape. It has high forming accuracy and is particularly suitable for special complex structures (such as overhanging structures, thin-walled structures, complex curved surfaces, spatial lattices, etc.) and the integrated design and printing of functional structures of complex components, so as to achieve advanced manufacturing of high-performance and multifunctional components.
[0003] Since SLM has a high cooling rate (~10 6 / s), large temperature gradient (~10 6 K / m) and more complex thermal history characteristics, the aluminum alloy used to prepare the complex microstructure fully reflects the cross-scale, multi-level and heterogeneous characteristics. Taking the SLM-formed AlSi10Mg alloy as an example, its microstructure spans 10 -10 ~10 -5The five orders of magnitude of m include four kinds of structural features that play an important role in macroscopic mechanical behavior: sub-nanometer supersaturated atoms and their clusters (Å), nanometer precipitated particles (nm), micrometer silicon-rich eutectic network (μm), and sub-micrometer grains and molten pools (μm). In recent years, nano-fine hard particle nucleating agents (such as TiN, TiC, TiB2, Al3Zr, Al3Sc, Al2Cu, etc.) are introduced into the SLM forming process of traditional high-strength 2xxx and 7xxx aluminum alloys to control the solidification process and form fine equiaxed grains, thereby effectively overcoming the extremely high crack sensitivity that is prone to occur in the SLM forming process of traditional high-strength 2xxx and 7xxx aluminum alloys, and strengthening the aluminum alloy by hindering dislocation movement. The Chinese patent document with publication number CN109175350 B discloses an Al-Mg-Mn-Sc-Zr aluminum alloy powder for additive manufacturing and a preparation method thereof, which refines the grains and improves the mechanical properties of printed parts by adding Sc and Zr elements as a modification agent for aluminum alloy. However, although Sc and Zr are added to the aluminum alloy powder of the invention, the tensile strength of the tensile test bar processed by the SLM additive manufacturing equipment is 450MPa, the mechanical properties are not high, and the strength does not exceed 500MPa. Moreover, the addition of the easily soluble Mg element will inevitably lead to a significant decrease in the thermal conductivity of the aluminum alloy. Therefore, it is urgent to provide a new type of aluminum alloy powder, and by optimizing the existing aluminum alloy composition and microstructure, develop a powder material suitable for additive manufacturing of high thermal conductivity and high strength functional structure integrated aluminum alloy components, fill the performance gap of yield strength above 650MPa and thermal conductivity above 190W / (m•K), and meet the weight reduction needs of replacing steel with aluminum in the fields of aerospace, rail transportation, communications and electronics. Summary of the invention
[0004] The primary purpose of the present invention is to provide an aluminum alloy powder for additive manufacturing.
[0005] To achieve the above object, the technical solution of the present invention is:
[0006] An aluminum alloy powder for additive manufacturing, the aluminum alloy powder is composed of AlTi x Fe y Ni z Co m Zr n Alloy particles and covered with AlTi x Fe y Ni z Co m Zr n The AlN flakes on the particle surface are composed of, by weight percentage, 1%≤x≤4%, 1%≤y≤5%, 1%≤z≤5%, 1%≤m≤5%, 0.1%≤n≤0.5%, and the balance is Al, wherein the AlN accounts for AlTix Fe y Ni z Co m Zr n 1.327% to 2.422% by weight; the AlTi x Fe y Ni z Co m Zr n The alloy particles are spherical with a particle size of 15~53μm, and the thickness of the AlN flakes is 80~500nm.
[0007] Another object of the present invention is to provide a method for preparing the aluminum alloy powder for additive manufacturing and application thereof, comprising the following steps:
[0008] (1) Press AlTi x Fe y Ni z Co m Zr n The raw materials aluminum block, titanium block, iron block, nickel block, cobalt block and Al-5wt.% Zr master alloy are weighed and put into an induction melting furnace, and melted under Ar gas protection to obtain an alloy melt;
[0009] (2) pouring the alloy melt obtained in step (1) into a tundish with a φ5 mm leak hole at the bottom through a draft tube under the protection of Ar gas, and simultaneously opening high-pressure nitrogen to atomize the alloy melt flowing out of the leak hole of the tundish to obtain spherical aluminum alloy powder;
[0010] (3) The spherical aluminum alloy powder obtained in step (2) is ball-milled for 5 to 10 hours in an argon-nitrogen mixed gas atmosphere, using a Φ5 mm cemented carbide grinding ball to obtain an aluminum alloy powder for additive manufacturing.
[0011] Furthermore, the pressure range of the protective gas Ar in step (1) is 1.0-1.2×10 5 Pa; the melting temperature range is 730~760℃.
[0012] Furthermore, in the step (2), the pressure range of the nitrogen is 1.5-3.5 MPa; and the atomizer used is a tightly coupled annular gap nozzle.
[0013] Furthermore, in the step (3), the volume ratio of argon to nitrogen in the argon-nitrogen mixed gas is 9:1-3, the pressure range of the mixed gas is 1.0-3.0 MPa, the weight percentage of the ball material is 10-20:1, and the speed of the ball mill is 500-1000 rpm.
[0014] A use of an aluminum alloy powder for additive manufacturing, wherein the aluminum alloy powder is used in a laser selective melting process in additive manufacturing; in the laser selective melting process, the laser power is 250-400W, the laser spot diameter is 60μm-80μm, the scanning speed is 800-1500mm / s, the layer thickness is 20-35μm, the scanning spacing is 20-40μm, and the interlayer rotation angle is 67°; the phase of the aluminum alloy sample obtained by the laser selective melting process includes a main phase and a reinforcement phase, and the main phase is α-A l matrix phase, the reinforcement phase includes petal-shaped Al3Ti coarse-grained phase, fibrous filamentous Al9(Fe,Co,Ni)2 fine-grained phase and lamellar AlN phase. The thermal conductivity of the aluminum alloy sample is 193~218W / (m·K), the yield strength is 652MPa~693MPa, and the elongation is 7.5%~10.2%, which meets the weight reduction demand of replacing steel with aluminum in the fields of aerospace, rail transportation, electronic communications, etc., and realizes the advanced manufacturing of high-strength and high-thermal conductivity functional structural integrated components.
[0015] Compared with the prior art, the present invention has the following advantages:
[0016] Different from the strengthening mechanism of traditional high-strength 2xxx series Al-Cu, 7xxx series Al-Zn alloys and aluminum alloys modified and strengthened by adding elements such as Sc and Zr to traditional aluminum alloys, the present invention provides a new type of aluminum alloy powder for additive manufacturing based on Al3Ti, Al9(Fe,Co,Ni)2 intermetallic compound strengthening and AlN in-situ strengthening mechanism. The present invention preferably uses Ti, Fe, Ni and Co as alloying elements. The aluminum alloy powder is composed of AlTi x Fe y Ni z Co m Zr n Alloy particles and covered with AlTi x Fe y Ni z Co m Zr n Spherical aluminum alloy powder composed of AlN flakes on the particle surface. Usually Ti, Fe, Ni and Co elements are added to cast aluminum alloy and solidified under normal conditions to form Al3Ti, Al9Co2, Al 13The coarse and brittle phases of low-symmetry intermetallic compounds such as Fe4 will lead to a decrease in the strength of the aluminum alloy. However, the petal-shaped Al3Ti phase and the fiber-like Al9(Fe,Co,Ni)2 phase formed in the laser rapid melting and solidification process of the present invention have a significant nanoscale heterogeneous microstructure, which contains a large number of dislocation defects, and together with a large number of AlN strengthening phases generated by in-situ reactions and dispersedly distributed, they exist in the aluminum alloy matrix in the form of nano-scale intermetallic compound sheets. At the same time, these nano-layered intermetallic compounds and a small amount of added Zr jointly promote the heterogeneous nucleation of Al grains during the laser rapid solidification process, and the Al grains are significantly refined. The combined force of dislocation strengthening, grain refinement strengthening and dispersion strengthening brings about a strengthening effect of a yield strength of more than 650MPa and an elongation of more than 7.5%. At the same time, the solid solubility of the added elements in the aluminum alloy is very low, and a high thermal conductivity of more than 190W / (m•K) is maintained.
[0017] The method of the present invention utilizes a mechanochemical reaction mechanism, high-pressure gas atomization and high-energy reaction ball milling process, and creatively provides an in-situ reaction preparation method for lamellar AlN flakes and aluminum alloy composite powders by regulating the volume ratio of nitrogen in the ball milling atmosphere, the ball milling time, the ball mill speed and the ball-to-material ratio. No other medium and high temperature conditions are required, and the controllable generation and dispersed distribution of AlN flakes are achieved. AlN with a thermal conductivity of 320 W / (m•K) can significantly improve the thermal conductivity and strength of aluminum alloys. The preparation method is simple, efficient, low-cost, and easy to mass produce.
[0018] The aluminum alloy sample block obtained by laser selective melting of the aluminum alloy powder of the present invention has a thermal conductivity of 193-218 W / (m·K), a yield strength of 652 MPa-693 MPa, and an elongation of 7.5%-10.2%, which meets the weight reduction demand of replacing steel with aluminum in the fields of aerospace, rail transportation, communications and electronics, and realizes the advanced manufacturing of high-strength and high-thermal conductivity functional structural integrated components. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a scanning electron microscope morphology image of the spherical gas atomized aluminum alloy powder in Example 1;
[0020] Figure 2 This is a scanning electron microscope morphology image of the spherical aluminum alloy powder in Example 1;
[0021] Figure 3 The scanning electron microscope microstructure image of the spherical aluminum alloy powder in Example 1 is magnified 18000 times;
[0022] Figure 4 This is a scanning electron microscope morphology image of the laser selectively melted aluminum alloy sample in Example 2, magnified 10,000 times. DETAILED DESCRIPTION
[0023] For a better understanding of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited to the description scope of the embodiments.
[0024] In the following embodiments of the present invention, the induction melting furnace used is composed of a melting power supply, an induction coil, a melting crucible, etc., which are located together with the tundish in a closed circular melting furnace body, and the furnace body is provided with vacuum and gas filling pipeline interfaces.
[0025] The induction melting furnace and atomizer used in the present invention are both within the scope of the prior art.
[0026] Example 1
[0027] According to the atomic ratio of Al: Ti: Fe: Ni: Co: Zr = 95.9: 1: 1: 1: 1: 0.1, weigh the raw materials of aluminum block, titanium block, iron block, nickel block, cobalt block and Al-5wt.% Zr master alloy with a purity of 99%. After loading, close the door of the induction melting furnace and evacuate the furnace to 1.0×10 -3 Pa, and fill the furnace with 1.0×10 5 Pa pressure Ar gas, under the protection of Ar gas, the temperature is raised to 730℃ for smelting to obtain alloy melt; the obtained alloy melt is poured into the middle package with a φ5mm leak hole at the bottom through the guide pipe under the protection of Ar gas, and at the same time, 1.5MPa nitrogen is opened to atomize the alloy melt flowing out of the leak hole of the middle package to obtain spherical aluminum alloy powder such as Figure 1 As shown, the atomizer used is a tightly coupled annular gap nozzle; after the atomization is completed, the obtained powder is cooled and ball milled for 5 hours in an argon-nitrogen mixed gas atmosphere with a volume ratio of argon to nitrogen of 9:1, the mixed gas pressure is 1.0MPa, the ball material weight percentage is 10:1, the ball mill speed is 500rpm, and the grinding balls used for ball milling are Φ5mm hard alloy grinding balls, and a spherical aluminum alloy powder with an AlN content of 1.327wt.% is obtained. The spherical powder with a particle size of 15~53μm obtained by the present invention is as follows Figure 2 As shown in the figure, it shows that the spherical atomized powder is repeatedly collided and rolled by high-energy cemented carbide during the ball milling process, resulting in angular and spheroidal morphology changes. Figure 3Scanning electron microscopy analysis magnified to 18,000 times showed that the rough powder particle surface was covered with AlN flakes with a thickness of 80 to 500 nm, indicating the occurrence of in-situ nitridation reaction. The laser selective melting process parameters for this type of spherical aluminum alloy particle powder used in additive manufacturing are shown as follows: laser power is 250W, laser spot diameter is 60μm, scanning speed is 800mm / s, layer thickness is 20μm, scanning spacing is 20μm, and interlayer rotation angle is 67°; the physical phase of the aluminum alloy specimen obtained by the laser selective melting process includes a main phase and a reinforcement phase. The main phase is an α-Al matrix phase, and the reinforcement phase includes a petal-shaped Al3Ti coarse-grained phase, a fibrous filament-like Al9(Fe,Co,Ni)2 fine-grained phase and a lamellar AlN phase. The thermal conductivity of the aluminum alloy specimen is 193W / (m·K), the yield strength is 652MPa, and the elongation is 10.2%, which meets the weight reduction needs of replacing steel with aluminum in the fields of aerospace, rail transportation, electronic communications, etc., and realizes the advanced manufacturing of high-strength and high-thermal conductivity functional structural integrated components. Example 2
[0028] According to the atomic ratio of Al: Ti: Fe: Ni: Co: Zr = 88.2: 2.5: 3: 3: 3: 0.3, weigh the raw materials of aluminum block, titanium block, iron block, nickel block, cobalt block and Al-5wt.% Zr master alloy with a purity of 99%. After loading, close the door of the induction melting furnace and evacuate the furnace to 1.0×10 -3 Pa, and fill the furnace with 1.1×10 5Pa pressure of Ar gas, under the protection of Ar gas, the temperature is raised to 750℃ for melting to obtain an alloy melt; the obtained alloy melt is poured into a tundish with a φ5mm leak hole at the bottom through a guide tube under the protection of Ar gas, and at the same time, 2.5MPa nitrogen is opened to atomize the alloy melt flowing out of the leak hole of the tundish to obtain spherical aluminum alloy powder, and the atomizer used is a tightly coupled annular gap nozzle; after the atomization, the obtained powder is cooled, and ball milled for 8h in an argon-nitrogen mixed gas atmosphere with a volume ratio of argon to nitrogen of 9:2, the mixed gas pressure is 2.0MPa, the weight percentage of the ball material is 15:1, the ball mill speed is 800rpm, and the grinding balls used for ball milling are Φ5mm cemented carbide grinding balls, to obtain spherical aluminum alloy powder with an AlN content of 1.874wt.%. The present invention produces quasi-spherical powders with a particle size of 15 to 53 μm, and the rough powder particle surface is covered with AlN flakes with a thickness of 80 to 500 nm. The laser selective melting process parameters for this type of spherical aluminum alloy powder used in additive manufacturing are as follows: laser power is 300 W, laser spot diameter is 70 μm, scanning speed is 1200 mm / s, layer thickness is 30 μm, scanning spacing is 30 μm, and interlayer rotation angle is 67°; the phases of the aluminum alloy sample obtained by the laser selective melting process include a main phase and a reinforcement phase, the main phase is an α-Al matrix phase, and the reinforcement phase includes a petal-shaped Al3Ti coarse-grained phase, a fibrous filament-shaped Al9(Fe, Co, Ni)2 fine-grained phase, and a flaky AlN phase such as Figure 4 As shown, the thermal conductivity of the aluminum alloy sample is 206W / (m·K), the yield strength is 675MPa, and the elongation is 9.1%, which meets the weight reduction needs of replacing steel with aluminum in the fields of aerospace, rail transportation, electronic communications, etc., and realizes the advanced manufacturing of integrated components with high strength, toughness and high thermal conductivity functional structures. Example 3
[0029] According to the atomic ratio of Al: Ti: Fe: Ni: Co: Zr = 80.5: 4: 5: 5: 5: 0.5, weigh the raw materials of aluminum block, titanium block, iron block, nickel block, cobalt block and Al-5wt.% Zr master alloy with a purity of 99%. After loading, close the door of the induction melting furnace and evacuate the furnace to 1.0×10 -3 Pa, and fill the furnace with 1.2×10 5Pa pressure of Ar gas, under the protection of Ar gas, the temperature is raised to 760 ℃ for smelting to obtain an alloy melt; the obtained alloy melt is poured into a tundish with a φ5mm leak hole at the bottom through a guide tube under the protection of Ar gas, and at the same time, 3.5MPa high-pressure nitrogen is opened to atomize the alloy melt flowing out of the leak hole of the tundish to obtain spherical aluminum alloy powder, and the atomizer used is a tightly coupled annular gap nozzle; after the atomization, the obtained powder is cooled, and ball milled for 10 hours in an argon-nitrogen mixed gas atmosphere with a volume ratio of argon to nitrogen of 3:1, the mixed gas pressure is 3.0MPa, the weight percentage of the ball material is 20:1, the ball mill speed is 1000rpm, and the grinding balls used for ball milling are Φ5mm cemented carbide grinding balls, to obtain spherical aluminum alloy particle powder with an AlN content of 2.422wt.%. The method obtains spherical powder with a particle size of 15 to 53 μm, and the rough powder particle surface is covered with AlN flakes with a thickness of 80 to 500 nm. The laser selective melting process parameters of this type of spherical aluminum alloy powder used in additive manufacturing are shown as follows: laser power is 400W, laser spot diameter is 80μm, scanning speed is 1500mm / s, layer thickness is 35μm, scanning spacing is 40μm, and interlayer rotation angle is 67°; the physical phase of the aluminum alloy sample obtained by the laser selective melting process includes a main phase and a reinforcement phase. The main phase is an α-Al matrix phase, and the reinforcement phase includes a petal-shaped Al3Ti coarse-grained phase, a fibrous filament-like Al9(Fe,Co,Ni)2 fine-grained phase and a lamellar AlN phase. The thermal conductivity of the aluminum alloy sample is 218W / (m·K), the yield strength is 693MPa, and the elongation is 7.5%, which meets the weight reduction needs of replacing steel with aluminum in the fields of aerospace, rail transportation, electronic communications, etc., and realizes the advanced manufacturing of high-strength and high-thermal conductivity functional structural integrated components. Comparative Example
[0030] According to the atomic ratio of Al: Ti: Fe: Ni: Co: Zr = 88.2: 2.5: 3: 3: 3: 0.3, weigh the raw materials of aluminum block, titanium block, iron block, nickel block, cobalt block and Al-5wt.% Zr master alloy with a purity of 99%. After loading, close the door of the induction melting furnace and evacuate the furnace to 1.0×10 -3 Pa, and fill the furnace with 1.1×10 5Pa pressure of Ar gas, under the protection of Ar gas, the temperature is raised to 750℃ for melting to obtain an alloy melt; the obtained alloy melt is poured into a tundish with a φ5mm leak hole at the bottom through a guide tube under the protection of Ar gas, and at the same time, 2.5MPa nitrogen is opened to atomize the alloy melt flowing out of the leak hole of the tundish to obtain spherical aluminum alloy powder, and the atomizer used is a tightly coupled annular gap nozzle; after the atomization, the obtained powder is cooled, and ball-milled for 8h in an argon atmosphere of 2.0MPa, the weight percentage of the ball material is 15:1, the speed of the ball mill is 800rpm, and the grinding balls used for ball milling are Φ5mm cemented carbide grinding balls, to obtain spherical aluminum alloy powder with a particle size of 15~53μm. The laser selective melting process parameters of this type of spherical aluminum alloy powder used in additive manufacturing are shown as follows: laser power is 300W, laser spot diameter is 70μm, scanning speed is 1200mm / s, layer thickness is 30μm, scanning spacing is 30μm, and interlayer rotation angle is 67°; the physical phase of the aluminum alloy specimen obtained by the laser selective melting process includes a main phase and a reinforcement phase. The main phase is an α-Al matrix phase, and the reinforcement phase includes a petal-shaped Al3Ti coarse-grained phase and a fibrous filament-shaped Al9(Fe,Co,Ni)2 fine-grained phase. The thermal conductivity of the aluminum alloy specimen is 179W / (m·K), the yield strength is 585MPa, and the elongation is 6.8%.
[0031] Comparative analysis of Example 2 and the comparative example shows that the lamellar AlN phase generated in situ by mechanochemical reaction not only significantly improves the thermal conductivity, but also disperses uniformly in the matrix as a strengthening phase, and prepares an aluminum alloy sample with extremely high strength and good toughness. Comparative analysis of Examples 1, 2 and 3 shows that by adjusting the volume ratio of nitrogen in the ball milling atmosphere, the ball milling time, the ball mill speed and the ball-to-material ratio, the mechanochemical reaction in situ generation of the AlN phase can be regulated. The preparation method is simple and controllable, and no other medium and high temperature conditions are required. The dispersed AlN phase with a thermal conductivity of 320W / (m•K) significantly improves the thermal conductivity and strength of the aluminum alloy.
Claims
1. An aluminum alloy powder for additive manufacturing, characterized in that: The aluminum alloy powder By AlTi x Fe y Ni z Co m Zr n Alloy particles and covered with AlTi x Fe y Ni z Co m Zr n The AlN flakes on the particle surface are composed of, by weight percentage, 1%≤x≤4%, 1%≤y≤5%, 1%≤z≤5%, 1%≤m≤5%, 0.1%≤n≤0.5%, and the balance is Al, wherein the AlN accounts for AlTi x Fe y Ni z Co m Zr n 1.327% to 2.422% by weight; the AlTi x Fe y Ni z Co m Zr n The alloy particles are spherical, with a particle size of 15-53 μm, and the thickness of the AlN flakes is 80-500 nm; The method for preparing aluminum alloy powder for additive manufacturing comprises the following steps: (1) Press AlTi x Fe y Ni z Co m Zr n The raw materials aluminum block, titanium block, iron block, nickel block, cobalt block and Al-5wt.% Zr master alloy are weighed and put into an induction melting furnace, and melted under Ar gas protection to obtain an alloy melt; (2) pouring the alloy melt obtained in step (1) into a tundish with a φ5 mm leak hole at the bottom through a draft tube under the protection of Ar gas, and simultaneously opening high-pressure nitrogen to atomize the alloy melt flowing out of the leak hole of the tundish to obtain spherical aluminum alloy powder; (3) ball milling the spherical aluminum alloy powder obtained in step (2) for 5 to 10 hours in an argon-nitrogen mixed gas atmosphere, using a Φ5 mm cemented carbide grinding ball to obtain an aluminum alloy powder for additive manufacturing; In the step (3), the volume ratio of argon to nitrogen in the argon-nitrogen mixed gas is 9:1-3, the pressure range of the mixed gas is 1.0-3.0 MPa, the weight percentage of the ball material is 10-20:1, and the speed of the ball mill is 500-1000 rpm.
2. The aluminum alloy powder for additive manufacturing according to claim 1, characterized in that: The pressure range of the protective gas Ar in step (1) is 1.0~1.2×10 5 Pa; the melting temperature range is 730~760℃.
3. The aluminum alloy powder for additive manufacturing according to claim 1, characterized in that: In step (2), the pressure range of the high-pressure nitrogen is 1.5-3.5 MPa; the atomizer used is a tightly coupled annular gap nozzle.
4. A use of the aluminum alloy powder for additive manufacturing as claimed in claim 1, characterized in that: The aluminum alloy powder is used in the laser selective melting process in additive manufacturing to prepare high-strength, high-toughness, high-thermal conductivity functional structural integrated aluminum alloy components.
5. The use of the aluminum alloy powder for additive manufacturing according to claim 4, characterized in that: The aluminum alloy sample obtained by the laser selective melting process includes a main phase and a reinforcement phase. The main phase is an α-Al matrix phase, and the reinforcement phase includes a petal-shaped Al3Ti coarse-crystalline phase, a fibrous filament-shaped Al9(Fe,Co,Ni)2 fine-crystalline phase and a flaky AlN nanophase. The thermal conductivity of the aluminum alloy sample is 193 to 218 W / (m·K), the yield strength is 652 MPa to 693 MPa, and the elongation is 7.5% to 10.2%.
Citation Information
Patent Citations
An Al-Mg-Mn-Sc-Zr aluminum alloy powder for additive manufacturing and its preparation method
CN109175350B
Core-shell alloy powder for additive manufacturing, an additive manufacturing method and an additively manufactured precipitation dispersion strengthened alloy component
CN110382138A
Aluminium alloy powder material for additive manufacturing, preparation method and application
CN110791686A
Preparation method of aluminum alloy / ceramic composite material with high strength and high thermal conductivity
CN112453400A